2018
DOI: 10.1371/journal.pone.0208551
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity and relationships of cauliflower (Brassica oleracea var. botrytis) inbred lines assessed by using SSR markers

Abstract: Inbred lines are important germplasm in cauliflower breeding programs. To understand the genetic diversity and relationships of cauliflower inbred lines, the use of simple sequence repeat (SSR) markers will be of great value for parental line selection and breeding strategy design. In this study, the genetic diversity and relationships of 165 cauliflower inbred lines primarily derived from southeast China were assessed using SSR markers. Forty-three SSR markers were polymorphic across these inbred lines and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
(32 reference statements)
5
25
2
2
Order By: Relevance
“…In the present study the PIC content of 87 polymorphic loci ranged from 0.24-0.80 (Table 6), which classified all the 87 loci (g-SSR and EST-SSRs) as slightly informative (1 primer cnu107), reasonably informative (12 primers) and highly informative markers (74 primers) as per PIC content (Table 6), suggesting their ability in genetic differentiation of CMS and DH lines of cauliflower under study. The mean PIC content of 0.63 in present investigation based on 87 g-SSR and EST-SSRs was higher than the mean PIC of 0.316 observed for 165 cauliflower inbred lines by Zhu et al [92] and 0.60 as recorded for 57 genotypes of Brassica oleracea comprising 51 cultivars of cauliflower by Zhao et al [93]. The higher PIC value for most of loci revealed wide genetic diversity in the studied parental CMS and DH lines.…”
Section: Discussioncontrasting
confidence: 83%
“…In the present study the PIC content of 87 polymorphic loci ranged from 0.24-0.80 (Table 6), which classified all the 87 loci (g-SSR and EST-SSRs) as slightly informative (1 primer cnu107), reasonably informative (12 primers) and highly informative markers (74 primers) as per PIC content (Table 6), suggesting their ability in genetic differentiation of CMS and DH lines of cauliflower under study. The mean PIC content of 0.63 in present investigation based on 87 g-SSR and EST-SSRs was higher than the mean PIC of 0.316 observed for 165 cauliflower inbred lines by Zhu et al [92] and 0.60 as recorded for 57 genotypes of Brassica oleracea comprising 51 cultivars of cauliflower by Zhao et al [93]. The higher PIC value for most of loci revealed wide genetic diversity in the studied parental CMS and DH lines.…”
Section: Discussioncontrasting
confidence: 83%
“…In the present study the PIC content of 87 polymorphic loci ranged from 0.24–0.80, which classified all the 87 loci (g-SSR and EST-SSRs) as slightly informative (1 primer cnu107), reasonably informative (12 primers) and highly informative markers (74 primers). The mean PIC content of 0.63 in present investigation based on 87 genomic-SSR and EST-SSRs was higher than the mean PIC of 0.316 observed for 165 cauliflower inbred lines by Zhu et al [84] and 0.60 as recorded for 57 genotypes of Brassica oleracea comprising 51 cultivars of cauliflower by Zhao et al [85]. The DH lines developed through microspore culture are very diverse from most of the CMS lines.…”
Section: Discussioncontrasting
confidence: 68%
“…PRINCIPAL COORDINATE ANALYSIS. PCA was chosen to complement the cluster analysis information and genetic relationships (Zhu et al, 2018). The PCA results for 100 accessions based on the genetic distance matrix data from the nine SSR markers is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a population structure analysis showed that five populations were obtained from the 100 Vitis accessions. However, there were a few discrepancies between the cluster analysis and the structure analysis, which might be because each accession was assigned a fixed branch by cluster analysis, whereas the structural analysis assigned individuals to groups based on the percentage of population members (Zhu et al, 2018). The admixture of all the populations might indicate gene flow in these accessions (Aradhya et al, 2013).…”
Section: Resultsmentioning
confidence: 99%